Poor Performance of Small, Medium, and Micro Enterprises in South Africa: What has Race and Apartheid Got to Do with it? - Tendai Makwara; Lucky Sibanda; Chux Gervase Iwu (Journal of Economics, Business, and Accountancy Ventura, 2023)
Small, medium, and micro enterprises (SMMEs) are expected to contribute significantly to South Africa’s socioeconomic development. Despite the various private and public institutional agencies in place to bolster the role of SMMEs, these SMMEs continue to perform poorly. The poor performance of SMMEs has been linked to race and apartheid. Through a literature review, this study explored this attribution of SMMEs’ poor performance to race and apartheid, considering that many argue that the apartheid legacy is the root of many challenges encountered by SMMEs. The results are, however, ambivalent. They suggest that, although apartheid and race remain critical issues in explaining some existing structural challenges that SMMEs encounter, their effects may have been superseded by other post-apartheid issues that undermine SMMEs’ performance. Specifically, apart from continuing influences of apartheid-era challenges such as race-based barriers to markets and access to financial support, present-day issues such as corruption, bad governance, ill-conceived business strategies, and infrastructure challenges negatively influence the performance of SMMEs. Addressing these multifaceted issues requires coordinated efforts from the government, the private sector, and other stakeholders to create a conducive environment for SMMEs’ growth and success. We, therefore, conclude that the causes of the poor performance of SMMEs in South Africa stretch beyond race and apartheid and call for an exhaustive analysis of broader issues that undermine SMMEs’ performance in South Africa.